The discovery of the tomb of the Great Army General Iwrhya: A quasi 3D Electrical Resistivity Tomography (ERT), Saqqara, Giza, Egypt - EL AGUIZY, Ola Mohamed; GOBASHY, Mohamed Mostafa; METWALLY, Ahmed; SOLIMAN, Khaled Soliman; EL-HASSANIN, Nader (Contributions to Geophysics and Geodesy, 2020)
A quasi 3D electrical resistivity (ERT) survey was undertaken at a UNESCO World Heritage site, Saqqara, Giza, Egypt, during a joint archaeological-geophysical mission from Cairo University. The main objective is to detect the locations of the subsurface archaeological tombs/or crypts and to allocate any possible archaeological bodies/features buried underneath the study area. In this survey, SYSCAL Pro system with 24 electrodes and a multi-core cable is used for automatic data acquisition of profiling data. The dipole–dipole array was used to enhance resolution, 14 resistivity lines are conducted during this Survey. The processed data were analysed in order to produce resistivity tomography (ERT) for qualitative and quantitative interpretations. Inversion of the ERT data identified variation of resistivity values and the expected locations of the underground galleries and highlight the presence of regular shape structures probably due to features of archaeological interest. Excavations made accordingly in the study area led to an interesting discovery of a tomb of the Great Army General, Iwrhya. The tomb is approximately 2000 years old as it covers the reigns of both Kings Seth I and Ramesses II. Using the 3D resistivity tomography with such a multi-electrode technique proved its efficiency and applicability for non-invasive archaeo-geophysical prospecting.